PERLINDUNGAN HUKUM TERHADAP PEKERJA SETELAH TERJADINYA PEMUTUSAN HUBUNGAN KERJA SECARA SEPIHAK PADA HOTEL FOUR SEASONS RESORT BALI DI SAYAN - Hendra Winata, I Ketut; Markeling, I Ketut; Dedy Priyanto, I Made (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013)
Labor problem is tend uncompleted until this time, although it have been effortto overcome it. Therefore this study will explain main issue of labor that occurred, asfollows: about termination of job relationship unilaterally then don’t ready to pay theworker right when termination of job relation. Then obstacles faced in give sanction tothe employers who break the law. And the most important about protection of theworker law that should accept after occurring termination of job relationship. Includingthe role of concerned service in fulfill of protection of the work law after occurtermination of work relationship.
Keywords: Labor Problem, Termination Of Work Relationship, Worker’s Right, Protection of law